Communications pretesting on the effectiveness of printed materials on Family Planning in Davao City - Palma, Flor Niño S.
This study was conducted in three barangays in Davao City namely; Catalunan Pequeño, Cabantian, and Bago Oshiro. There were a total of 120 respondents who participated in the assessment of the printed materials on family planning. The main objective of this study is to measure the components of effectiveness namely; comprehension, attractiveness, acceptability, involvement, and inducement to action through communication pretesting. Intended audiences differ the way they process information and each audience segment has its own family planning goals and reproductive needs that actually influence how they comprehend, accept, relate, could be attracted, involved and persuaded to various health messages communicated to them. Female audience segment possibly processed persuasive messages in a central route that explains why they were motivated to comprehend and accepted the health information. On the contrary, male audience segment likely processed information in a peripheral route that probably resulted to low mental effort in message elaboration, low acceptability, involvement, and inducement rates after evaluating the content of the IEC material. However, psychological and socio-cultural factors also influenced the way they respond to the health information.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts